The study of heat treatment activities in Malaysia / Muhammad Noor Harun and Hisham Abdul Wahab - Harun, Muhammad Noor; Abdul Wahab, Hisham (Faculty of Mechanical Engineering, 1994)
This final project report entitled “The Study of Heat Tratment Activities in Malaysia”. The research was conducted out for a duration of six months. It was started in the middle of October 1993 and ended in the end of March 1994. This study is all directed to give the ideas of how advance and the development of the heat treatment activities as well as methods in Malaysia…